Preventing payments fraud in the FinTech era: New evidence from a behavioural experiment - Jesper Akesson; John Gathergood; Edika Quispe-Torreblanca (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2023)
Innovation in financial technology has granted consumers increased access to faster, more convenient payment services. This development has, however, also given rise to Authorised Push Payment (APP) fraud, where consumers are unwittingly manipulated into authorising transactions to counterfeit parties, such as fake online sellers. The annual costs of APP fraud are growing, and for example total more than 0.5bn in the United Kingdom alone. In this paper, we present the results from an online experiment that tests interventions designed to reduce the likelihood that consumers fall for APP fraud. These interventions were presented to consumers within a mobile bank application, and for instance, involved presenting warnings and increasing the salience of calls-to-action. Our analysis shows that redesigned calls-to-action can dramatically reduce fraud success rates, whereas traditional behavioural and risk-based warnings have much weaker effects. Our results show how redesigning consumer journeys can potentially reduce fraud prevalence.
Keywords: G21; G41; G5; 330; fraud; financial technology; behavioural science